Polar-coordinate line-projection light-curing continuous 3D printing for tubular structures - Huiyuan Wang; Siqin Liu; Xincheng Yin; Mingming Huang; Yanzhe Fu; Xun Chen; Chao Wang; Jingyong Sun; Xin Yan; Jianmin Han; Jiping Yang; Zhijian Wang; et al. (International Journal of Extreme Manufacturing, 2024)
3D printing techniques offer an effective method in fabricating complex radially multi-material structures. However, it is challenging for complex and delicate radially multi-material model geometries without supporting structures, such as tissue vessels and tubular graft, among others. In this work, we tackle these challenges by developing a polar digital light processing technique which uses a rod as the printing platform. The 3D model fabrication is accomplished through line projection. The rotation and translation of the rod are synchronized to project and illuminate the photosensitive material volume. By controlling the distance between the rod and the printing window, we achieved the printing of tubular structures with a minimum wall thickness as thin as 50 micrometers. By controlling the width of fine slits at the printing window, we achieved the printing of structures with a minimum feature size of 10 micrometers. Our process accomplished the fabrication of thin-walled tubular graft structure with a thickness of only 100 micrometers and lengths of several centimeters within a timeframe of just 100 s. Additionally, it enables the printing of axial multi-material structures, thereby achieving adjustable mechanical strength. This method is conducive to rapid customization of tubular grafts and the manufacturing of tubular components in fields such as dentistry, aerospace, and more.